Burden of dengue among febrile patients at the time of chikungunya introduction in Piedecuesta, Colombia. Issue 11 (19th September 2018) - Carabali, Mabel; Lim, Jacqueline K.; Palencia, Diana C.; Lozano‐Parra, Anyela; Gelvez, Rosa Margarita; Lee, Kang Sung; Florez, Janeth P.; Herrera, Victor Mauricio; Kaufman, Jay S.; Rojas, Elsa M.; Villar, Luis Angel
Abstract: Objective: To estimate the age‐specific incidence of symptomatic dengue and chikungunya in Colombia. Method: A passive facility‐based fever surveillance study was conducted among individuals with undifferentiated fever. Confirmatory diagnostics included serological and molecular tests in paired samples, and surveillance's underreporting was assessed using capture–recapture methods. Results: Of 839 febrile participants 686 completed the study. There were 33.2% (295/839) dengue infections (51% primary infections), and 35.9% (191/532) of negative dengue cases there were chikungunya cases. On average, dengue cases were younger (median = 18 years) than chikungunya cases (median = 25 years). Thrombocytopaenia and abdominal pain were the main dengue predictors, while presence of rash was the main predictor for chikungunya diagnosis. Underreporting of dengue was 31%; the estimated expansion factors indicate an underreporting rate of dengue cases of threefold for all cases and of almost sixfold for inpatients. Conclusions: These findings highlight the ongoing coexistence of both arboviruses, a distinct clinical profile of each condition in the study area that could be used by clinicians to generate a differential diagnosis, and the presence of underreporting, mostly among hospitalised cases.